Acute health effects of accidental chlorine gas exposure - Kim, Joo-An (Ann Occup Environ Med, 2014)
OBJECTIVES: This study was conducted to report the course of an accidental release of chlorine gas that occurred in a factory in Gumi-si, South Korea, on March 5, 2013. We describe the analysis results of 2 patients hospitalized because of chlorine-induced acute health problems, as well as the clinical features of 209 non-hospitalized patients. METHODS: We analyzed the medical records of the 2 hospitalized patients admitted to the hospital, as well as the medical records and self-report questionnaires of 209 non-hospitalized patients completed during outpatient treatment. RESULTS: Immediately after the exposure, the 2 hospitalized patients developed acute asthma-like symptoms such as cough and dyspnea, and showed restrictive and combined pattern ventilatory defects on the pulmonary function test. The case 1 showed asthma-like symptoms over six months and diurnal variability in peak expiratory flow rate was 56.7%. In case 2, his FEV1 after treatment (93%) increased by 25% compared to initial FEV1 (68%). Both cases were diagnosed as chlorine-induced reactive airways dysfunction syndrome (RADS) on the basis of these clinical features. The most frequent chief complaints of the 209 non-hospitalized patients were headache (22.7%), followed by eye irritation (18.2%), nausea (11.2%), and sore throat (10.8%), with asymptomatic patients accounting for 36.5%. The multiple-response analysis of individual symptom revealed headache (42.4%) to be the most frequent symptom, followed by eye irritation (30.5%), sore throat (30.0%), cough (29.6%), nausea (27.6%), and dizziness (27.3%). CONCLUSIONS: The 2 patients hospitalized after exposure to chlorine gas at the leakage site showed a clinical course corresponding to RADS. All of the 209 non-hospitalized patients only complained of symptoms of the upper airways and mucous membrane irritation.